Investigação do papel do sistema endocanabinoide nos efeitos induzidos pelo exercício físico de alta intensidade em um modelo animal de inflamação crônica periférica - Lüdtke, Daniela Dero (2017)
Endocannabinoids (ECBs) have emerged as a promising approach in the treatment of chronic pain, since the activation of their receptors exerts neuromodulatory, anti-inflammatory and vasodilatory effects, thus promoting analgesia. These effects are also promoted by physical exercise that, depending on the intensity, increases the blood concentrations of ECBs. Objective: The present study investigated the role of the ECB system in the effects induced by high intensity swimming in an animal model of chronic peripheral inflammation. Methods: Of the experimental type, this study used male Swiss mice (25-35g) kept under similar conditions in the Laboratory of Experimental Neurosciences (LaNEx) of UNISUL. Peripheral chronic inflammation was induced by intraplantar (i.pl.) injection containing 20μl of 80% complete Freud adjuvant (CFA) solution. In different experiments, 192 mice were used, allocated to groups of animals (n = 8), not exercised and exercised. The animals that were exercised were submitted to seven days of high intensity swimming and the hiponociceptive and antiedematogenic effects of swimming were analyzed by the von Frey test and paw thickness measurements, respectively. In order to verify the involvement of cannabinoid receptors (CBs) type 1 and 2, selective antagonists for CB1 (AM281) and CB2 (AM630) receptors were administered systemically and at peripheral and central sites, prior to swimming. In the analysis of the involvement of ECB degradation enzymes, selective inhibitors of fatty acid amidohydrolase – FAAH (URB937) – and monoacylglycerol lipase – MAGL (JZL184) – were administered systemically. Results: High intensity swimming induced hyponociception and reduced edema in animals; the pretreatment of animals with AM281 or AM630 prevented swimming-induced hyponociception; the pre-administration of URB937 or JZL184 prolonged swimming-induced hyponociception. Conclusion: High intensity swimming induces hyponociception and reduces edema in animals with chronic peripheral inflammation. The activation of CB1 and CB2 receptors, as well as the prolongation of hyponociception by the inhibition of ECB degradation enzymes confirms the participation of the ECB system in swimming-induced hyponociception.